Environmental History: Complex Connections around the Constancy of Change (Historia, 2021)
EnglishThis article has been adapted from a paper presented in the Ruth Edgecombe Environmental Challenges Lecture Series, University of KwaZulu-Natal, Pietermaritzburg, on 1 October 2008. It outlines the contribution of Professor Edgecombe to the study of environmental history in South Africa. Using the title of Edgecombe's book, The Constancy of Change: A History of Hlobane Colliery, 1898-1998 (1998) as the over-arching metaphor, the article celebrates the links that Edgecombe was so adept at making and to explore the nature and challenges of environmental history. The author stresses how nexus between nature and culture - the "connections" between regions, timescales, disciplines and biota - are at the core of the subdiscipline and illuminate previously neglected aspects of human and natural history. As is explained, environmental historians have been able to engage with the changes in the urgency of environmental concerns and to address issues such as climate change, genetically modified foods, animal ethics and other challenges of the twenty-first century.   AfrikaansOmgewingsgeskiedenis: Ingewikkelde Ineenskakeling om Voortdurende VeranderingHierdie artikel is ƌ aangepaste weergawe van ƌ lesing wat gehou is as deel van die Ruth Edgecombe Omgewingsuitdagingslesingsreeks, aangebied deur die Universiteit van KwaZulu-Natal, Pietermaritzburg, op 1 Oktober 2008. Dit skets die bydrae van professor Edgecombe tot die bestudering van omgewingsgeskiedenis in Suid-Afrika. Deur die titel van haar boek, The Constancy of Change A History of Hlobane Colliery, 1898-1998 (1998) as oorkoepelende metafoor te gebruik, vier die artikel die ineenskakelings wat Edgecombe met soveel vaardigheid kon maak om die aard van en uitdagings wat omgewingsgeskiedenis bied, te ondersoek. Die skrywer beklemtoon hoe die verband tussen natuur en kultuur – die verbintenisse tussen streke, tydskale, dissiplines en biota – die kern van die sub-dissipline vorm, en werp die lig op voorheen afgeskeepte aspekte van menslike en natuurgeskiedenis. Soos verduidelik word, was omgewingsgeskiedkundiges in staat om by veranderinge in terme van die dringendheid van omgewingskwessies soos klimaatsverandering, geneties veranderde voedselsoorte, diere etiek en ander uitdagings van die een-en-twintigste eeu betrokke te raak.
Keywords: Environmental history; historiography; interdisciplinary; Ruth Edgecombe; Historiografie; interdissiplinêr; omgewingsgeskiedenis